2016
DOI: 10.1590/1980-5373-mr-2015-0643
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Co and Zn Addition on Densification and Electrical Properties of Ceria-Based Nanopowders

Abstract: In this work, cobalt and zinc-doped Ce 0.8 Gd 0.2 O 1.9 samples were prepared starting from a commercial nanopowder and compared to the undoped material. The powder samples were pressed and afterwards sintered by a two-step procedure, before characterization by X-Ray Diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and Impedance Spectroscopy (IS) in air. Cobalt or zinc additions are effective as sintering aid, allowing peak si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Nevertheless, the composition is not the only pertinent parameter, and the link between microstructure and electrochemical properties of SOFC materials have been widely studied: tuning of the microstructure, and more precisely of the grains size, has been reported, either by changing the calcination temperature for LSCF perovskite anodes [21] and LSF cathodes [22] for instance, or by changing the pressure and temperature of sintering by spark plasma sintering for LSZO electrolyte material [23]. It has been shown that the microstructure of BCZY derivatives can be controlled by varying synthesis routes [24][25][26][27][28][29][30][31], tuning the composition including additional elements [32,33] or adding sintering aids [27,[34][35][36][37][38][39][40], with a balance between grain and grain boundary contributions which have been in some cases separated by using electrochemical impedance spectroscopy (EIS) [15,41].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the composition is not the only pertinent parameter, and the link between microstructure and electrochemical properties of SOFC materials have been widely studied: tuning of the microstructure, and more precisely of the grains size, has been reported, either by changing the calcination temperature for LSCF perovskite anodes [21] and LSF cathodes [22] for instance, or by changing the pressure and temperature of sintering by spark plasma sintering for LSZO electrolyte material [23]. It has been shown that the microstructure of BCZY derivatives can be controlled by varying synthesis routes [24][25][26][27][28][29][30][31], tuning the composition including additional elements [32,33] or adding sintering aids [27,[34][35][36][37][38][39][40], with a balance between grain and grain boundary contributions which have been in some cases separated by using electrochemical impedance spectroscopy (EIS) [15,41].…”
Section: Introductionmentioning
confidence: 99%
“…Nicholas and De Jonghe [18] compared the effect of many elements (additives) on the densification of GDC, and the highest densification values were obtained with the addition of Li, Zn, Co, and Cu. Most studies on sintering aids for doped-ceria were focused on pellets densification and characterization of their electrical conductivity [19][20][21][22][23][24][25], with the aim to build anode supported cells with doped-ceria electrolytes, but few papers addressed the influence of these sintering aids on the electrode performance when used as additives in GDC interlayers. As the Co addition in GDC has been widely studied [26][27][28], we focused our efforts on the three other candidates, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the addition of sintering additives can decrease the conductivity of the electrolyte, especially in the presence of SiO 2 impurities by increasing the grain boundary resistance [266]. For example, it was reported that cobalt oxide and copper oxide are useful additives in promoting the sinterability of ceria solid solutions (i.e., GDC); however, most of the added cobalt and copper ions were found to segregate at the grain boundaries [267,268]. When studying the microstructure and conductivity of doped ceria, background impurities, such as SiO 2 , are of major concern.…”
Section: Doped Ceriamentioning
confidence: 99%